The Effect of Game Development-Based Learning on the Development of Problem Solving Skills of Multimedia Vocational Students - Farhan Abdul Azis; Agus Juhana; Nurhidayatulloh, Nurhidayatulloh (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Learning that focuses on game development is increasingly accepted as an innovative approach to improve students' problem-solving skills, especially in Multimedia Vocational High Schools (SMK). This study aims to investigate the impact of game-based learning on students' problem-solving skills and compare it with traditional learning methods. Through systematic literature analysis, it was found that educational games such as Kahoot!, Quizlet, Minecraft: Education Edition, and Duolingo can not only increase students' motivation but also encourage active engagement in the learning process. Game-based learning provides a platform for students to experience real-world problem-solving scenarios in an interactive and collaborative environment. Furthermore, the creative process involved in game development helps students enhance their critical thinking and technical skills. The results showed that students who engaged in game-based learning development tended to have better problem-solving skills compared to students who used conventional methods. This research emphasizes the importance of game integration in education to maximize students' potential in facing challenges in the working world. It also highlights the need for educators to adapt and innovate teaching methods to align with the demands of the digital era, ensuring that students are well-prepared for future career challenges.